SiCLAT: simultaneous imaging of chromatin loops and active transcription in living cells - Xin Wan; Jie Kong; Xiaodi Hu; Lulu Liu; Yuanping Yang; Hu Li; Gaoao Liu; Xingchen Niu; Fengling Chen; Dan Zhang; Dahai Zhu; Yong Zhang (Genome Biology)
Abstract We present SiCLAT, which introduces a dCas9-dCas13d cassette into the mouse genome. This model enables the stable expression of both dCas9 and dCas13 proteins in diverse cell populations, facilitating concurrent labeling of DNA and RNA across various cell types. Using SiCLAT, we accurately labeled chromatin loop anchor interactions and associated gene transcription during myogenic differentiation. This imaging system offers a novel means of directly observing cis-element interactions and the corresponding gene transcription in living primary cells, thus providing real-time imaging for comprehensive mechanistic investigations of dynamic enhancer-promoter or enhancer-enhancer interactions in regulating transcription activation within living cells.